混沌优化方法及其在机械工程优化设计中的应用 - 冯春; 陈永 (Jixie Chuandong, 2003)
The chaos pattern optimization algorithm is proposed, which is a global optimization method, and consists of two kinds of two kinks of moves, one called the chaos exploratory move and the other called the pattern search. The numerical simulation result shows that the method is effective.